Reduction of 1-alkyl/aryl-3-(4-alkyl-5-alkylimino-Δ2-1,2,4-thiadiazolin-3-yl) thioureas: Formation of 1,3,5-triazine-2-thiones - R. Surve, Satish; V. Nair, Sheena (Asian Journal of Chemistry, 2016)
Reduction of 1-alkyl/aryl-3-(4-alkyl-5-alkylimino-Δ2-1,2,4-thiadiazolin-3-yl) thioureas in a basic medium yields 1,3-diakyl-4-alkyl/arylimino-6-iminohexahydro-1,3,5,-triazine-2-thiones. The structure assigned to these triazines was based on the substituent pattern on the chain formed by the ring opening and its reaction towards alkali.